An in-situ synchrotron diffraction study of stress relaxation in titanium: Effect of temperature and oxygen on cold dwell fatigue. (July 2021) - Xiong, Yi; Karamched, Phani S.; Nguyen, Chi-Toan; Collins, David M.; Grilli, Nicolò; Magazzeni, Christopher M.; Tarleton, Edmund; Wilkinson, Angus J.
Graphical abstract: Abstract: There is a long-standing technological problem in which a stress dwell during cyclic loading at room temperature in Ti causes a drastic fatigue life reduction. To better understand the material characteristics that control or exacerbate this behaviour, evaluation of the time dependent plasticity of the main prismatic and basal slip systems is critical. Incorporating the influence of operating temperatures and common alloying elements on cold dwell fatigue will be beneficial for future alloy design to address this problem. In this work, characterisation of the time dependent plastic behaviour of two commercially pure titanium samples (grade 1 and grade 4) with different oxygen content at 4 different temperatures (room temperature, 75  ° C, 145  ° C and 250  ° C ) was performed during stress relaxation using synchrotron X-ray diffraction. Key parameters that govern the dislocation motion were determined for the major prismatic and basal slip systems as a function of temperature and oxygen content by calibrating a crystal plasticity finite element model with the measured lattice strain relaxation responses. From the temperatures assessed, 75  ° C was found to be the worst-case scenario, where the macroscopic plastic strain accumulation was significant during a relaxation cycle due to the greatest activity of both prism and basal slip systems. As the temperature increases, the contribution of thermal energy becomes greater than mechanical energy for dislocation glide. Oxygen was found to have a stronger strengthening effect on prism slip over basal slip, through a significant change in their respective critical resolved shear stresses. This effect becomes more significant in high oxygen content commercially pure Ti.